The Challenges of Bridging the Research–Practice Gap through Insider–Outsider Partnerships in Education. Issue 12 (December 2019) - Phelps, David
Background: Partnerships between schools and universities are increasingly advocated as a way to bridge the research–practice gap in education. Empirical research has revealed a wide variety of benefits that these partnerships can bring to merging research and practice. Yet, empirical studies also demonstrate that merging research and practice through partnerships at local sites is neither straightforward nor a guaranteed process. Rather, it is a fragile process fraught with tension that often stems from the relationship between the school and university partners. Purpose: Kornfeld and Leyden reflected that if schools and universities are to successfully partner, they "should be ever mindful of … the infinite complexities and potential pitfalls in the relationship." The purpose of this literature review is to document these complexities and pitfalls more fully so that schools and universities involved in partnerships can have more realistic expectations of the demanding work entailed in maintaining healthy relationships. Realistic expectations can help school and university partners to more successfully navigate the fragility of their work. Furthermore, the research literature suggests that when partners work collaboratively to address these challenges, they will strengthen their relationships. Research Design: A literature review was conducted using an intellectual social network analysis and an extensive database search. A total of 56 studies were selected for analysis using relevant inclusion and exclusion criteria. Findings: The 56 studies reveal that challenges to maintaining partnerships emerge from the differences in schools and universities along three high-level categories: organizational structures, discourse practices, and power relations. Yet, schools and universities can mitigate these challenges by working together to collaboratively build organizational infrastructure, shared meaning, and trusting relationships. Recommendations: Schools and universities that partner to close the gap between research and practice at local sites should be mindful of the ways that their differences in organizational structures, discourse practices, and power relations can complicate their work together. At the same time, schools and universities can strengthen their relationships by intentionally working to collaboratively build organizational infrastructure, shared meaning, and trusting relationships. By working to reconcile the differences between themselves, schools and universities can better learn how to navigate the fragility inherent in their partnership.